Analysis of Factors Affecting Quality Regional Government Financial Report In Indonesia - Hendrik Gamaliel; Rudy Johanis Pusung; Priscillia Weku (AIBPM Publisher, 2026)
This study aims to see the influence of human resource competence, information technology, leadership support, and leadership commitment on the quality of financial reports. This study used individual samples of ASN employees at BPKAD of North Sulawesi Province and Bali Province. Data was collected by distributing questionnaires via Google Forms. 100 questionnaires were analyzed using Validity, Reliability, and Ordinary Least Squares (OLS) Tests. The study's results indicate that human resource capability positively and significantly affects the quality of financial reports. The study's results indicate that the sophistication of information technology has a positive and significant impact on the quality of financial reports. The study results indicate that leadership support positively and significantly impacts the quality of financial reports. The results of the survey indicate that leadership commitment has a positive and significant impact on the quality of financial reports